Finding a needle in a stick of needles? Teaching phraseological units with modern poetry - Bernstein, Nils (2018)
According to Guillermo Cabrera Infante (Cabrera Infante, 1967, p. 221) language is a forest of words. The Cuban author also stated in his novel Tres tristes tigres: Sometimes using the right phraseological unit is not as difficult as finding a needle in a haystack, which would be comparatively easy, but rather as difficult as finding a needle in a stack of needles. Corpas Pastor (2003, p. 109) simply asserts: “[L]a fraseología [...] está de moda”. And still today phraseology is relevant especially in the didactics of foreign languages. In a first step, we will illustrate benefits of incorporating literature in language classes in general. Afterwards we show these benefits of using the example of the Chilean poet Nicanor Parra (1914-2018) and the Austrian writer of experimental poetry Ernst Jandl (1925-2000). Concluding with a synthesis, two projects are introduced: the minimum of phraseological units that are to be learned and the project of Widespread Idioms in Europe and Beyond.